2017
DOI: 10.1177/1747954117732725
|View full text |Cite
|
Sign up to set email alerts
|

Groupness, cohesion, and intention to return to sport: A study of intact youth teams

Abstract: The positive benefits for youth participating in sport have been well documented. Yet, keeping athletes returning to sport has been a concern. While various factors have been examined to explain this attrition, facets of the sport group experience have started to emerge. From a group perspective, it has been established that athlete intentions to return to a sport team the following season are positively associated with perceived team cohesion. While cohesion is a key group construct, other group factors are w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Adapting the questionnaire into Portuguese required certain contextual modifications to the original to ensure that the translation had the highest possible item comprehension for the sample of 12–19 years old Portuguese athletes. From a descriptive standpoint, athletes reported high average levels of cohesion, with slightly higher task than social cohesion perceptions, which aligns with other youth sport studies that have employed the YSEQ (McLaren et al, 2015, 2017; McLaren & Spink, 2016; Spink et al, 2018; Taylor & Bruner, 2012). The reliability and validity results support the YSEQ on psychometric and construct validity grounds.…”
Section: Discussionsupporting
confidence: 84%
“…Adapting the questionnaire into Portuguese required certain contextual modifications to the original to ensure that the translation had the highest possible item comprehension for the sample of 12–19 years old Portuguese athletes. From a descriptive standpoint, athletes reported high average levels of cohesion, with slightly higher task than social cohesion perceptions, which aligns with other youth sport studies that have employed the YSEQ (McLaren et al, 2015, 2017; McLaren & Spink, 2016; Spink et al, 2018; Taylor & Bruner, 2012). The reliability and validity results support the YSEQ on psychometric and construct validity grounds.…”
Section: Discussionsupporting
confidence: 84%
“…The results from Study 2 also demonstrated that role commitment was positively correlated with intentions to return to sport in a non-Canadian context, which may have implications for researchers concerned with prolonged sport participation. Declines in adherence rates in youth sport has been an item of concern for researchers and practitioners (Spink et al, 2018; ParticipACTION, 2018). As a result, many have examined group-related perceptions in relation to adherence perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers employing an earlier five-item unidimensional measure of groupness reported a positive association between groupness and physical activity behavior (Spink et al, 2010). Youth sport researchers employing the same tool in experimental and correlational studies also revealed an interaction between sport team cohesion and groupness: Athletes reported increased intentions to return to highly cohesive teams, but primarily when those teams were ascribed high groupness (Spink, McLaren, & Ulvick, 2018; Spink, Ulvick, McLaren, Crozier, & Fesser, 2015).…”
Section: Advancing Groupness Research: Motivational and Behavioral Co...mentioning
confidence: 96%